Charlie Chaplin and A Woman of Paris: The Genesis of a Misunderstood Masterpiece (MCFARLAND & CO INC, 2021)
Charlie Chaplin's A Woman of Paris (1923) was a groundbreaking film which was neither a simple recycling of Peggy Hopkins Joyce's story, nor quickly forgotten. Through heavily-documented “period research,” this book lands several bombshells, including Paris is deeply rooted in Chaplin’s previous films and his relationship with Edna Purviance, Paris was not rejected by heartland America, Chaplin did “romantic research” (especially with Pola Negri), and Paris' many ongoing influences have never been fully appreciated. These are just a few of the mistakes about Paris.
https://katalog.adlr.link/Record/51-9781476672441